Uji Efektivitas Gel Ekstrak Etanol Daun Asam Jawa dalam Proses Penyembuhan Luka Bakar pada Tikus Jantan - Tiara Fortuna A.R; Muhammad Yunus; Astriani Natalia Br Ginting (Pusat Riset dan Inovasi Nasional, 2025)
Burn injuries are a significant health problem because they damage the skin’s protective barrier, increase the risk of infection, and may cause severe complications if not treated properly. The healing process is complex and involves several cellular events, in which fibroblasts play a key role by producing collagen and forming granulation tissue. Recently, there has been growing interest in natural, herbal-based therapies for wound care. Tamarind leaves (Tamarindus indica) were chosen in this study because they contain flavonoids, polyphenols, tannins, and saponins, all of which have anti-inflammatory, antioxidant, and tissue-regenerating properties. The aim was to evaluate the effectiveness of ethanol extract gel of tamarind leaves at concentrations of 2.5%, 5%, and 10% in promoting fibroblast proliferation and healing of burn wounds in male rats (Rattus norvegicus). An experimental randomized design was used with six groups: normal control, neative control, positive control, and three treatment groups. Clinical observation and histopathological analysis showed that the extract gel accelerated wound closure significantly compared to the negative control. Fibroblast proliferation was higher in all treatment groups, with the 10% extract giving the best result, similar to Bioplacenton. These findings highlight tamarind leaves’ potential as a safe and affordable alternative for burn wound therapy.